Luxury Box E-Commerce Website And Simulation With MP2 System - Saeed Adel Alkatheri; Cahyo Darujati; Ani Wulandari (NAROTAMA UNIVERSITY, 2023)
Electronic commerce or E-commerce is the media through which people can do the business activities or business process online with the help of internet. In this process buying of goods, selling of products or serve services for business are under one roof means there is no need to go outside for buying any product or selling any product, each and every business transaction can do online through computer. Luxury box is an online shop that was founded in 2020. The researcher observe that there was a lack of online promotions to introduce new potential customers at the online shop and managing product by the owner, therefore the researcher used the MP2 system to build the website. The data collections are observation and Interview. The researcher is focused on convenience and security that can provide smoothness for luxury box customers. The research methodology used is qualitative research. The results of this study are in the form of a website that is supported by WordPress version 6.0.1 technology. The web pages contained in the website are generally divided into 2 (two) parts, the dashboard page that is used by the admin to manage the content that will be displayed on the website, website page that displays the results of content management created by the admin and can be accessed by website visitors.